Right to Sanitation: Case Study of Indonesia - Devi Triasari (Lembaga Contrarius Indonesia, 2021)
Sanitation is a basic human right which shows that someone is dignified and deserves to be respected as a human being. The international community has recognized the importance of this right. However, this right has not been explicitly recognized. This is because the legal status of the right to sanitation is unclear. The right to sanitation is derived from the